2018
DOI: 10.1177/0361198118768530
|View full text |Cite
|
Sign up to set email alerts
|

Latent Hazard Anticipation in Young Drivers: Review and Meta-Analysis of Training Studies

Abstract: Young drivers are overrepresented in motor vehicle crashes, and are shown to be poorer at anticipating potential threats on the roadway compared with their more experienced peers. Literature demonstrates the effectiveness of driver training programs at improving young drivers’ latent hazard anticipation performance. Various hazard anticipation training studies have been undertaken on different population demographics using different training scenario presentation modes and multiple evaluation testbeds. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Pradhan and colleagues [6] then developed a computer-based program, Road Awareness and Perception Training (RAPT) [8], which aimed to increase the anticipatory glances toward latent hazards through an error-based training feedback approach [9]. RAPT allows trainees to make errors (Mistake), correct their behavior (Mitigate) and learn the correct behavior (Mastery), or 3M approach as previously defined in the driver training literature (e.g., [6,10]). A subsequent on-road evaluation showed that the RAPT-trained drivers anticipated the hazard more accurately than the Placebo-trained drivers (M = 64% vs. 37%).…”
Section: Introductionmentioning
confidence: 99%
“…Pradhan and colleagues [6] then developed a computer-based program, Road Awareness and Perception Training (RAPT) [8], which aimed to increase the anticipatory glances toward latent hazards through an error-based training feedback approach [9]. RAPT allows trainees to make errors (Mistake), correct their behavior (Mitigate) and learn the correct behavior (Mastery), or 3M approach as previously defined in the driver training literature (e.g., [6,10]). A subsequent on-road evaluation showed that the RAPT-trained drivers anticipated the hazard more accurately than the Placebo-trained drivers (M = 64% vs. 37%).…”
Section: Introductionmentioning
confidence: 99%
“…Two independent (double blind) raters coded whether participants correctly looked at the target zone while driving through the launch zone, which was predetermined for each scenario. This protocol has been used in previous hazard anticipation evaluations (Unverricht et al, 2018) The parameters of each launch zone were discussed prior to coding. Videos that had been previously coded in Yamani et al (2018) were re-coded by the raters to ensure consistency.…”
Section: Methodsmentioning
confidence: 99%
“…Newly licensed young drivers (in the 16-17 age range) are most at risk of failing to recognize hidden hazards out of all age groups, but young drivers (19-29 years old) are still significantly worse at recognizing latent hazards than older adults (60-75 years old) (Pradhan et al, 2005). Many training programs geared towards young novice drivers have focused on addressing hazard anticipation errors via a variety of modalities, such as expert narration, computer-based trainings and desktop-simulator programs, which have demonstrated both short-term and long-term success in improving hazard anticipation behavior (Unverricht, Samuel & Yamani, 2018;McDonald, Goodwin, Pradhan, Romoser, & Williams, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Risk Awareness and Perception Training (RAPT) is one such training and has been shown to improve latent hazard anticipation skills in young drivers, evaluated both in driving simulators and on the road (Fisher et al, 2007). Latent hazard anticipation is usually measured by the proportion of latent hazards that were visually fixated on by the driver when going through the road environment (Unverricht et al, 2018). The benefits of RAPT can persist up to six months after initial training, demonstrating the retention of latent hazard anticipation skills (Taylor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%